STUDI TENTANG KERAJINAN ROTAN SILUNGKANG KOTA SAWAHLUNTO - WENNY DAMELA PUTRI, Drs. Erwin A, M.Sn., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2017)
The purpose of this study was to describe the craft Rattan Silungkang Kota Sawahlunto. This research is a descriptive qualitative research. Sources of data in this study are products of rattan (primary data) and informants, and literature (secondary data). Data collection procedures done through observation, interviews and documentation study. Based on the results of the study, concluded the following. The conclusions of the study: 1) Engineering workmanship rattan is still done manually, and traditional (hereditary) using simple equipment. 2) The shape of rattan produced entirely in 3-dimensional shapes, such as household products. 3) motif on the rattan arising from the use of matting techniques, depending on taste and creativity of individual craftsmen. 4) The process of finishing in the given lacquered rattan cane to be more durable is not eaten by termites. Advice to future researchers to investigate further, so that the information rattan Silungkang more complete.Kata kunci: rotan, kerajinan rotan , silungkang